A Family of Stationary Solutions to the Euler Equations and Generalized Solutions - Precioso, Juliana Conceição (CUBO, A Mathematical Journal, 2010)
In this work, we present a interesting family of stationary solutions for the Euler equations, which behaves in the same way that the approximated solutions presented in [6].